2022
DOI: 10.3389/fcvm.2021.788703
|View full text |Cite
|
Sign up to set email alerts
|

Change in Computed Tomography-Derived Fractional Flow Reserve Across the Lesion Improve the Diagnostic Performance of Functional Coronary Stenosis

Abstract: Aims: This study sought to evaluate the diagnostic performance of change in computed tomography-derived fractional flow reserve (CT-FFR) across the lesion (ΔCT-FFR) for identifying ischemia lesions with FFR as the reference standard.Methods: Patients who underwent coronary CT angiography (CCTA) and FFR measurement within 1 week from December 2018 to December 2019 were retrospectively enrolled. CT-FFR within 2 cm distal to the lesion, ΔCT-FFR and plaque characteristics were analyzed. The diagnostic accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Consistent with the findings of Takagi et al ( 9 ), our previous study ( 11 ) also showed ΔFFR CT had a higher diagnostic performance than FFR CT (AUC, 0.743 vs. 0.803, P<0.001, respectively) . As a non-invasive alternative to IVUS, CCTA-based coronary plaque characteristics had been shown to be associated with ischemia by several non-invasive imaging studies ( 6 , 18 , 22 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with the findings of Takagi et al ( 9 ), our previous study ( 11 ) also showed ΔFFR CT had a higher diagnostic performance than FFR CT (AUC, 0.743 vs. 0.803, P<0.001, respectively) . As a non-invasive alternative to IVUS, CCTA-based coronary plaque characteristics had been shown to be associated with ischemia by several non-invasive imaging studies ( 6 , 18 , 22 ).…”
Section: Discussionsupporting
confidence: 90%
“…The value of FFR CT was measured within 2 cm distal to the lesion plaque, which was colocalized with the invasive FFR. ΔFFR CT was defined as the change in the FFR CT across the lesion by computing the difference between the proximal and distal FFR CT values as follows (9)(10)(11): ΔFFR CT = proximal FFR CT − distal FFR CT . To assess the reproducibility between the observers, 2 experienced radiologists measured the ΔFFR CT of 30 consecutive vessels without knowledge of the patients' conditions.…”
Section: Ffrct Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, they demonstrated that the choice of virtual FFR measurement locations is particular importance when identifying ischemic lesions or guiding treatment strategies [13][14][15]. Series studies demonstrated that lesion-speci c FFR, such as lesion-speci c CT-FFR, can reclassify positive patients de ned by the vesselderived FFR value, and that lesion-speci c FFR has higher diagnostic performance than vessel-derived FFR [29][30][31][32]. The possiable causes of the above phenomennon were as follows: 1) the virtual FFR measurement at far distal segments may overeatimate coronary ischemia, 2) these differences between vessel territories in pressure gradients for segments 1-2 cm distal to the stenosis versus far distal segments relate to the larger territory of perfused myocardium, 3) the virtual FFR were only assessed in the main coronary arteries, which may have disregarded the impact of collateral stenosis on myocardial ischemia [6,14].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in CT-FFR (i.e., ΔCT-FFR) of the MBs were also measured. ΔCT-FFR was de ned as the difference in CT-FFR values between the proximal and distal ends of the MB [19]. Both sets of CCTA data (optimal systole and optimal diastole) were used for the calculation of CT-FFR of the MBs.…”
Section: Calculation Of Ct-ffr Of Myocardial Bridgesmentioning
confidence: 99%